Efek Perbedaan Media Quenching pada Sifat Mekanik Baja Karbon Aisi 1045 - Mohamad Agus Fhaizal; S. Sunyoto (TECHNO-SOCIO EKONOMIKA, 2025)
AISI1045 steel is widely used as an automotive component for example for gear components in motorized vehicles. In its application steel type AISI 1045 must have resistance and hardness to wear. This study aims to determine the effect of cooling media on hardness and depth of hardness and microstructure of Steel AISI 1045. The material is heat treated hardening Flame using oxy-acetylen gas with a holding time of 1 minute 30 seconds and quenching with a variety of cooling media (Water, Oil 10W40, and Oil 20W / 50) and holding time 1 hour. From the water cooling media produced the highest average hardness of 62.78 HRA, and the smallest was 52.34 HRA on oil cooling media 20W / 50. The results of the microstructure showed differences in grain size and number of porosity where the water cooling medium has a smaller grain size compared to 10W40 Oil cooling media, and 20W / 50 Oil and more porosity is found in water cooling media. From the results of the SEM test with 1000x magnification obtained the value of the depth of hardness using a mathematical approach with water cooling medium has the highest depth of 0.037 mm. This is because the water viscosity is lower compared to 10W / 40 Oil cooling media and 20W / 50 Oil so that the water cooling media produces a higher hardness value to Steel AISI 1045.